A scoping review of trials of interventions led or delivered by cancer nurses. (October 2018) - Charalambous, Andreas; Wells, Mary; Campbell, Pauline; Torrens, Claire; Östlund, Ulrika; Oldenmenger, Wendy; Patiraki, Elisabeth; Sharp, Lena; Nohavova, Iveta; Domenech-Climent, Nuria; Eicher, Manuela; Farrell, Carole; et al.
Abstract: Background: Advances in research and technology coupled with an increased cancer incidence and prevalence have resulted in significant expansion of cancer nurse role, in order to meet the growing demands and expectations of people affected by cancer (PABC). Cancer nurses are also tasked with delivering an increasing number of complex interventions as a result of ongoing clinical trials in cancer research. However much of this innovation is undocumented, and we have little insight about the nature of novel interventions currently being designed or delivered by cancer nurses. Objectives: To identify and synthesise the available evidence from clinical trials on interventions delivered or facilitated by cancer nurses. Data sources and review methods: A systematic review of randomised controlled trials (RCT), quasi-RCTs and controlled before and after studies (CBA) of cancer nursing interventions aimed at improving the experience and outcomes of PABC. Ten electronic databases (CENTRAL, MEDLINE, AMED, CINAHL, EMBASE, Epistemonikos, CDSR, DARE, HTA, WHO ICTRP) were searched between 01 January 2000 and 31 May 2016. No language restrictions were applied. Bibliographies of selected studies and relevant Cochrane reviews were also hand-searched. Interventions delivered by cancer nurses were classified according to the OMAHA System. Heat maps were used to highlight the volume of evidence available for different cancer groups, intervention types and stage of cancer care continuum. Results: The search identified 22, 450 records; we screened 16, 169 abstracts and considered 925 full papers, of which 214 studies (247, 550 participants) were included in the evidence synthesis. The majority of studies were conducted in Europe (n = 79) and USA (n = 74). Interventions were delivered across the cancer continuum from prevention and risk reduction to survivorship, with the majority of interventions delivered during the treatment phase (n = 137). Most studies (131/214) had a teaching, guidance or counselling component. Cancer nurse interventions were targeted at primarily breast, prostate or multiple cancers. No studies were conducted in brain, sarcoma or other rare cancer types. The majority of the studies (n = 153) were nurse-led and delivered by specialist cancer nurses (n = 74) or advanced cancer nurses (n = 29), although the quality of reporting was poor. Conclusions: To the best of our knowledge, this is the first review to synthesise evidence from intervention studies across the entire cancer spectrum. As such, this work provides new insights into the nature of the contribution that cancer nurses have made to evidence-based innovations, as well as highlighting areas in which cancer nursing trials can be developed in the future.